Use of percutaneous endoscopic colostomy (PEC) to treat sigmoid volvulus: a systematic review - Frank, Lucinda; Moran, Alex; Beaton, Ceri (Endoscopy International Open, 2016)
Background and aim: Percutaneous endoscopic colostomy provides an alternative management option for patients with recurrent sigmoid volvulus who are considered too high risk to undergo surgery. We reviewed the literature to assess whether the National Institute for Health and Clinical Excellence guidelines published in 2006 supporting the use of percutaneous endoscopic colostomy are still valid. Methods: A systematic literature search was conducted using PubMed, Web of Science, and Embase. The exploded search terms “Percutaneous Endoscopic Colostomy” and “Sigmoid Volvulus” were used. Librarian support was used to ensure the maximum number of relevant articles were returned. Identified abstracts were then analyzed and included if they met the inclusion criteria. Results: Five observational studies and 5 case reports were identified that met the inclusion criteria. They provided data on 56 patients with recurrent sigmoid volvulus treated with percutaneous endoscopic colostomy placement. Sixteen of the 56 patients were treated with a single percutaneous endoscopic colostomy (PEC) tube while 38 patients were treated with 2 PEC tubes. For 2 patients the details of the procedure were unknown. Five patients developed major complications following the procedure: 1 patient developed peritonitis after 4 days, due to fecal contamination secondary to tube migration and 2 patients with cognitive impairment pulled their PEC tubes out. Two other patients died following PEC insertion. Nine patients developed minor complications following the procedure. The most commonly reported minor complication was infection at the PEC site. Four of 56 patients developed a recurrent sigmoid volvulus with a PEC tube in situ. Conclusion: Although in these case series there is a 21 % risk of morbidity and 5 % risk of mortality from the use of a PEC, this is favorable compared to the mortality risk of 6.6 % to 44 % reported with operative intervention. This review of contemporary literature therefore supports the use of PEC in frail and elderly patients.